2023
DOI: 10.1021/acs.jctc.3c00198
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Simulation of Multiphase Coexistence in Biomolecular Mixtures

Abstract: Biomolecular condensates constitute a newly recognized form of spatial organization in living cells. Although many condensates are believed to form as a result of phase separation, the physicochemical properties that determine the phase behavior of heterogeneous biomolecular mixtures are only beginning to be explored. Theory and simulation provide invaluable tools for probing the relationship between molecular determinants, such as protein and RNA sequences, and the emergence of phase-separated condensates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 157 publications
1
11
0
Order By: Relevance
“…The actual calculation involves a choice for the values of each of the N ( N + 1)/2 virial coefficients B ij . This choice can either be based on the physical properties of the components and determined experimentally or estimated theoretically or alternatively be obtained through a priori assumptions on the statistical distribution of the virial coefficients . The present paper provides a procedure to determine the spinodal and critical points using eqs and , where the calculation is achieved by choosing S c,ij or S sp, ij in the range ⟨−∞,∞⟩ (although the transformation of the parameter space strongly restricts these ranges, as illustrated for N = 3 and positive virial coefficients in the Results section).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The actual calculation involves a choice for the values of each of the N ( N + 1)/2 virial coefficients B ij . This choice can either be based on the physical properties of the components and determined experimentally or estimated theoretically or alternatively be obtained through a priori assumptions on the statistical distribution of the virial coefficients . The present paper provides a procedure to determine the spinodal and critical points using eqs and , where the calculation is achieved by choosing S c,ij or S sp, ij in the range ⟨−∞,∞⟩ (although the transformation of the parameter space strongly restricts these ranges, as illustrated for N = 3 and positive virial coefficients in the Results section).…”
Section: Discussionmentioning
confidence: 99%
“…This choice can either be based on the physical properties of the components and determined experimentally or estimated theoretically or alternatively be obtained through a priori assumptions on the statistical distribution of the virial coefficients. 18 The present paper provides a procedure to determine the spinodal and critical points using eqs 20 and 26 , where the calculation is achieved by choosing S c,ij or S sp, ij in the range ⟨−∞,∞⟩ (although the transformation of the parameter space strongly restricts these ranges, as illustrated for N = 3 and positive virial coefficients in the Results section). For physically relevant solutions, the choices of S c,ij or S sp, ij should lead to non-negative coordinates c i,c or c i ,sp —something that can be confirmed easily by substituting the selected S c,ij or S sp, ij in eq 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have demonstrated that this approach can efficiently converge the Pareto front for a pair of biophysical properties that depend on a complex sequence of computations. We anticipate that this framework could be applied to other combinations of biophysical traits and may also be useful for studying multicomponent and multiphasic systems ( 78 80 ). Our work therefore establishes a promising approach for engineering custom biomolecular condensates with tunable thermodynamic and dynamic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The premise of the RMT is that if the random matrix is large enough, the actual values of B ij typically do not matter anymore and only their average and standard deviations are of importance, and for some aspects, even the details of the distribution itself do not play a role anymore. It is not completely clear, however, which simplifications in the calculations are driven by mathematical convenience and which ones are driven by physical relevance, thus yielding some words of caution while applying the RMT approach, as was also mentioned by Jacobs (2023). The exact analytical expressions given in Table 2 allow us to separate the mathematical aspects of the RMT approach from the physical aspects in the calculation.…”
Section: Figurementioning
confidence: 98%